Economic rationales for investments in science - Hans Gersbach; Ulrich Schetter; Maik T. Schneider (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
What is the economic rationale for investing in science? Based on an open economy model of creative destruction, we characterize four key factors of optimal investment in basic research: the stage of economic development, the strength of the manufacturing base, the degree of openness, and the share of foreign-owned firms. For each of these factors, we analyse its bearings on optimal basic research investment. We then show that the predicted effects are consistent with patterns observed in the data and discuss how the factor-based approach might inform basic research policies.
Keywords: H41; O38; 330; Basic Research; Economic Growth; Growth Policy